Reactions to gender egalitarian men: Perceived feminization due to stigma-by-association. (September 2013) - Rudman, Laurie A.; Mescher, Kris; Moss-Racusin, Corinne A.
Gender egalitarian men are vital for women's progress, yet attitudes toward and beliefs about them are underinvestigated. In three experiments, women liked gender egalitarian men more so than men did, but both genders stigmatized them as more feminine, weak, and likely to be gay, compared with control male targets. This was true even when the gender egalitarian was an actual presidential candidate for the American Psychological Association (Experiment 3). We examined whether stigmatization was due to (a) gender egalitarians' presumed affiliations with women and/or gay men (stigma-by-association); (b) the gay male feminist stereotype; or (c) a threat to men's gender identity. Results supported stigma-by-association, but only for affiliations with women (not gay men). The gay male feminist stereotype was robust, but did not account for stigmatization, and men's reactions to male gender egalitarians were independent of their gender identity. Implications of these findings for gender equality are discussed.